2016
DOI: 10.1038/ncomms12650
|View full text |Cite
|
Sign up to set email alerts
|

Stereotyped initiation of retinal waves by bipolar cells via presynaptic NMDA autoreceptors

Abstract: Glutamatergic retinal waves, the spontaneous patterned neural activities propagating among developing retinal ganglion cells (RGCs), instruct the activity-dependent refinement of visuotopic maps. However, its initiation and underlying mechanism remain largely elusive. Here using larval zebrafish and multiple in vivo approaches, we discover that bipolar cells (BCs) are responsible for the generation of glutamatergic retinal waves. The wave originates from BC axon terminals (ATs) and propagates laterally to near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 55 publications
5
47
0
Order By: Relevance
“…A form of retinal waves have also been described in zebrafish (Zhang et al, 2016). However they do not appear to be present in amphibians, which are able to rely on photoreceptor-driven vision from the onset of development of the retinotectal projection.…”
Section: In the Absence Of Sensory Input Correlated Spontaneous Fmentioning
confidence: 99%
See 3 more Smart Citations
“…A form of retinal waves have also been described in zebrafish (Zhang et al, 2016). However they do not appear to be present in amphibians, which are able to rely on photoreceptor-driven vision from the onset of development of the retinotectal projection.…”
Section: In the Absence Of Sensory Input Correlated Spontaneous Fmentioning
confidence: 99%
“…This study revealed that the initiation point of the waves is biased to the ventrotemporal region of the retina, an observation that is particularly interesting in light of the fact that a locomoting fish or tadpole in the wild would typically experience natural visual stimuli as optic flow similarly sweeping from temporal to nasal retina, further arguing that retinal waves may have evolved as a replacement for natural vision prior to eye-opening. Retinal waves in zebrafish also stereotypically originate from the temporal retina (Zhang et al, 2016). In tadpoles, it has been shown directly that visual stimulation which includes optic flow in this more natural direction is far more effective at refining the retinotopic projection of RGCs than an identical amount of stimulation oriented in the opposite direction (Hiramoto and Cline, 2014).…”
Section: In the Absence Of Sensory Input Correlated Spontaneous Fmentioning
confidence: 99%
See 2 more Smart Citations
“…This has been postulated to be driven primarily by hardwired molecular cues (Nevin et al, 2008). However, waves of spontaneous activity that propagate across the retina are also thought to play a significant role in this tectal patterning (Zhang et al, 2016). Hence, the relative influence of both evoked retinal input and spontaneous retinal activity on spontaneous activity within the tectum remains unclear.…”
Section: Introductionmentioning
confidence: 99%